Exploration of the Mechanisms of Differential Indole Alkaloid Biosynthesis in Dedifferentiated and Cambial Meristematic Cells of Catharanthus roseus Using Transcriptome Sequencing - Zhou, Pengfei; Chen, Mingxiang (Frontiers in Genetics, 2022)
Catharanthus roseus produces terpenoid indole alkaloids (TIAs) of high medicinal importance. The current research focuses on finding an efficient production system such as cell suspension cultures for high TIA concentrations. Catharanthus roseus cambial meristematic cells (CMCs) offer multiple advantages over dedifferentiated cells (DDCs) regarding growth, homogeneity, and shear resistance. Our lab has established a CMC culture system induced by C. roseus cambium. We determined the concentrations of TIAs in CMCs and DDCs. CMCs produced significantly higher concentrations of total alkaloids, vindoline, vinblastine, catharanthine, and ajmalicine as compared to DDCs. We then performed Illumina HiSeq transcriptome sequencing of CMCs and DDCs and explored the differential transcriptomic signatures. Of the 96,004 unigenes, 9564 were differentially expressed between the two cell suspension types. These differentially expressed genes (DEGs) were enriched in 137 KEGG pathways. Most importantly, genes from the indole alkaloid biosynthesis and the upstream pathways i.e., tryptophan metabolism, monoterpenoid biosynthesis, tropane, piperidine, and pyridine alkaloid biosynthesis, and terpenoid backbone biosynthesis showed differential transcriptomic signatures. Remarkably, the expression of genes associated with plant hormone biosynthesis, signaling, and MAPK signaling pathways was re-latable to the different TIA concentrations in CMCs and DDCs. These results put forward multi-ple target genes, transcription factors, and regulators to develop a large-scale TIA production system using C. roseus CMCs.